Comparing the effect of miniscrew-supported and conventional maxillary incisor intrusion on the inclination of maxillary incisors and molars - A systematic review and meta-analysis - Himali Gupta; Arpit Gupta; Sanjeev Verma; Satinder Pal Singh (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of this study was to compare the effect of miniscrew-supported maxillary incisor intrusion and conventional intrusion mechanics on maxillary incisors and molar inclination. Material and Methods: Search databases (PubMed, Scopus, Web of Science, Embase, EBSCOhost, and the Cochrane Library) were searched for randomized trials on intrusion of maxillary incisors via miniscrew-supported and conventional mechanics. The revised Cochrane risk-of-bias tool for randomized trials (RoB 2.0) was used. Five outcomes ([i] inclination change of upper incisors, [ii] inclination change of upper molars, [iii] intrusion of incisors, [iv] vertical change in upper first molars, and [v] overbite correction achieved) were statistically pooled using Review Manager 5.3. Subgroup analysis was conducted to receive sturdiness in meta-analysis. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation. Results: Out of 1777 studies, 7 were finally subjected to quality assessment, and 6 were included in the meta-analysis. The incisor inclination following maxillary incisor intrusion increased in miniscrew-supported intrusion in comparison to Connecticut intrusion arch (CTA) subgroup with standard mean difference of 0.66 mm (95% confidence interval = 0.16, 1.03, I2 = 0%). All the included studies showed an increase in molar inclination (distal tipping) in the CTA subgroup compared to the micro-implant group. Of all the seven included studies, only one study was identified with some concerns for the risk of bias, and the other six were judged to have an overall high risk of bias. Conclusion: The incisal proclination during deep-bite correction by miniscrew-supported incisal intrusion is more than that in the CTA subgroup; however, the difference may not be clinically very relevant. There is a very low quality of evidence in favor of miniscrew-supported intrusion as compared to conventional intrusion, necessitating the need for good-quality trials.